THE EFFECTIVITY OF EUTECTIC MIXTURE OF LOCAL ANESTHETICS CREAM AS EXTRACORPOREAL SHOCKWAVE LITHOTRIPSY ADJUVANT ANALGESIA IN SOETOMO GENERAL HOSPITAL - Sholihin, Riza Mazidu; Hakim, Lukman; M. Soebadi, Doddy (Indonesian Urological Association, 2019)
Objective: The Extracorporeal Shockwave Lithotripsy (ESWL) procedure is the first choice for kidney stone therapy with the size ≤20mm. One of the complications of ESWL is the pain. Pain control during ESWL is essential to maintain the focus point of ESWL and give enough time to achieve complete stone fragmentation. Until now there is still no data about the effectiveness of Eutectic Mixture of Local Anesthetics (EMLA) cream as an adjuvant analgesic for ESWL procedure in Soetomo Hospital Surabaya. To compare the onset of pain and ESWL Wong-Baker Pain Scale (WBPS) between the EMLA group and placebo group. Material & Methods: The design of this study was a single-blind randomized control trial comparing the onset of pain and Wong Baker pain scale between the patient in EMLA group and placebo one. WBPS is assessed in minute 15, 30, 45, and 60 of ESWL sessions and 60 minutes post ESWL procedure. The results were analyzed with SPSS. Pain onset and differences of WBPS were tested by using independent T-test if the data is normally distributed and using Mann-Whitney test if the data is not normally distributed. Results: 10 patients were obtained in each group. The mean onset of pain in the EMLA group was longer than the mean onset of pain in the placebo group but statistically not significant (p>0.05). The WBPS in the EMLA group was significantly lower compared with the placebo group in the 30, 45, and 60 minutes of ESWL (p<0.05). Conclusion: EMLA cream application before ESWL was effective and safe as an adjuvant analgesic to reduce pain during ESWL.